Analisis Status Gizi Dan Kadar Hemoglobin Terhadap Taksiran Berat Janin Pada Ibu Hamil Trimester III - Arief Adi Saputro; Catur Retno Lestari (Jurnal Kesehatan Masyarakat Celebes, 2022)
The accuracy of the estimate of the baby's birth weight is one of the most important measurements at the beginning of labor so that appropriate action can be taken to reduce the risk of complications for pregnant women and babies as early as possible. Pregnant women with iron deficiency anemia that can be caused include: premature parturition, LBW to the occurrence of perinatal death and inhibition of fetal growth and development. The purpose of this study was to determine the effect of nutritional status and hemoglobin levels on estimated fetal weight in third semester pregnant women. This research uses cross sectional approach and analytic observational method. The research location was conducted at the Level 1 Health Facility in Kudus Regency during July 2022. Data was collected by conducting research directly and measuring LILA using the LILA tape and Hb levels using easy touch. Estimated Fetal Weight is the estimated weight of the fetus in the womb with the measurement criteria for Estimated Fetal Weight using a metlin measuring instrument. The technique used as a sample determination is a total sampling technique of 32 third trimester pregnant women. Analysis of the data used is the Spearman Rank test through SPSS ver 23 software with sig. p<0.05. Based on the Spearman rank correlation test, it has a value of 0.098 and has a unidirectional relationship. A significance value of 0.595 > (α 0.05) means that there is no significant effect of nutritional status (LILA) on the estimated fetal weight in third trimester pregnant women. Furthermore, Spearman's rank correlation test has a value of 0.049 and has a unidirectional relationship. A significance value of 0.788 > (α 0.05) has no significant effect of nutritional status (LILA) on estimated fetal weight in third trimester pregnant women. there is no effect of nutritional status (LILA) and Hb levels on estimated fetal weight in third trimester pregnant women. It is recommended for pregnant women to carry out regular and periodic health checks and ANC.